The Framework and Types of Chemical Literacy Tests: A Systematic Review - Marfuatun Marfuatun; Nahadi Nahadi; Galuh Yuliani; Hernani Hernani (Postgraduate, University of Mataram, 2024)
The development of chemical literacy measurement instruments is influenced by changes and progress in frameworks, methods, and educational technologies. The study aimed to investigate the framework and test types that are utilized to measure students’ chemical literacy levels. With adherence to the PRISMA 20202, thirty-five empirical studies published between 2014 and 2023 are analyzed to find publication characteristics, chemical literacy frameworks, and test types. The finding showed that most publications were recorded in 2019, and the respondents who were involved in the research in the largest number are high school students, descriptive and experimental research are popular choices for researchers. The vast majority of studies develop chemical literacy tests using PISA and Shwartz et al frameworks and open-ended questions. Moreover, further research ought to inquire into the implementation of the chemical literacy test and integrate innovative technology of testing